Penilaian Kinerja Tenaga Pemasaran Untuk Menentukan Reward dan Benefit dengan Menggunakan Metode Weighted Product - Nabilah, Jihan; Ade Syahputra; Budi Arifitama (STMIK Budi Darma, 2024)
Employees are one of the most important assets a company has in its efforts to sustain its business. In this regard, employee management and employee performance assessment are very important to measure human resource management governance in order to achieve the company's goals, vision and mission. Many employees are affected by one individual whose performance declines. As a result, it will also affect the performance of a company. To maintain the performance of the company and employees, namely by providing the best rewards and benefits. Determining rewards and benefits must go through a work assessment or evaluation process. Therefore, it is necessary to analyze employee performance using the Weighted Product method. This method is able to complete employee performance analysis supported by historical data such as achievement, absenteeism, honesty, communication and cooperation. In this research, we try to find criteria that can be used to provide value to employee performance. In addition, a system will be designed that can speed up the provision of value to employees in the form or design model in the form of a Decision Support System (DSS), with the hope that the process or mechanism for providing value to employee performance will run more quickly and precisely. This increasing PT XYZ productivity and supporting the company's future development. It is hoped that the results of this research can help provide solutions regarding rewards and benefits for PT XYZ employees according to their performance